The Effectiveness of The Search Solve Create Share (SSCS) Learning Model to Improve The Mathematical Problem-Solving Ability of Students of SMA Negeri 1 Benai Kuansing - Nurhasikin, Nurhasikin; Armis, Armis; Yuanita, Putri (FKIP-Universitas Riau, 2024)
The motivated of this research is the low level of mathematical problem-solving ability of students at SMAN 1 Benai Kuansing. The purposes of this research are: 1) to describe the differences in mathematical problem-solving skills of students who study through the SSCS model with students who study through learning with a scientific approach; and 2) to examine the improvement in mathematical problem-solving skills of students who study through the SSCS model and students who study through learning with a scientific approach. This research is an experimental research (quasi experiment) with the Nonequivalent Pretest-Posttest Control Group Design. The result showed that the improvement in mathematical problem-solving ability of students who study through the SSCS model is higher than that of students who study through learning with a scientific approach. The conclutions is; 1)There is a significant average difference between the mathematical problem-solving abilities of students who follow the SSCS learning model and those of students who follow learning with a scientific approach; 2) Improvement the mathematical problem-solving ability of students who follow the SSCS learning model is better than improvement the mathematical problem-solving ability of students who follow learning with a scientific approach.